HUBUNGAN WAKTU PEMASANGAN KB IUD PASCASALIN DENGAN KEJADIAN EKSPULSI DI RS X - sagita, widi (Jurnal Ilmiah Kesehatan BPI, 2022)
ABSTRACT IUD expulsion is the occurrence of expulsion of the device from the uterus which usually occurs in the first trimester after insertion. Factors that influence the success of the IUD insertion are the type of IUD, the acceptor factor, the time of insertion (interval, postpartum, post-abortion, post-coitus), and the installation force. Based on a preliminary study at the X Hospital, the incidence of post placental and postpartum expulsion was 7% of 142 IUD acceptors in 2019, and 9% of 150 IUD acceptors in 2020. The purpose of this study was to determine the relationship between the timing of post-partum IUD insertion with expulsion incidence at X Hospital Period January-March 2021. Method This research is a descriptive analytic study with a cross sectional design, using a total sample of 78 respondents, using secondary data (medical records), analysis using SPSS. From the results of the study, the chi-square statistical test showed that there was a relationship between the timing of post-partum IUD insertion and the incidence of expulsion at the X Hospital for the period January-March 2021 (p-value = 0.047) with the highest incidence of expulsion at the time of post-placental insertion. Of the three variables, all of them have a relationship with the incidence of expulsion at the X Hospital for the January-March 2021 period. Keywords: Post partum IUD KB, Expulsion